High‐Performance Solution‐Processable N‐Shaped Organic Semiconducting Materials with Stabilized Crystal Phase. (8th May 2014) - Mitsui, Chikahiko; Okamoto, Toshihiro; Yamagishi, Masakazu; Tsurumi, Junto; Yoshimoto, Kazumi; Nakahara, Katsumasa; Soeda, Junshi; Hirose, Yuri; Sato, Hiroyasu; Yamano, Akihito; Uemura, Takafumi; Takeya, Jun
<x xml:space="preserve">Abstract</x> N‐shaped organic semiconductors are synthesized via four steps from a readily available starting material. Such semiconductors exhibit preferable ionization potential for p‐type operation, thermally stable crystalline phase over 200 °C, and high carrier mobility up to 16 cm2 V–1 s–1 (12.1 cm2 V–1 s–1 on average) with small threshold voltages in solution‐crystallized field‐effect transistors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>